HUBUNGAN ANTARA UMUR IBU DENGAN KEJADIAN PLASENTA PREVIA PADA IBU HAMIL DI RSUD BANYUMAS - Iik Hikmawatun Amalah; Prasanti Adriani (Universitas Harapan Bangsa Purwokerto, 2011)
he frequency of placenta previa in developing countries ranges from 1 to 2.4%,the maternal mortality rate due to placenta previa approximately 0.1 to 5%, while theperinatal mortality rate due to placenta previa around 7-25%.Objective: To determine the relationship between mother's age with the incidence of placentaprevia in pregnant women in Banyumas General Hospital in 2010. This study was cross sectional with retrosfektif approach based on secondary data,the sampling technique using total sampling technique, which uses data retrieved medicalrecords of all pregnant women who visited hospitals in Banyumas in 2010 about 2935pregnant women. The results of this study are of a total sample of 2395 pregnant women aged 20-35years with as many as 1918 people, while pregnant women with age <20 were 106 peopleand> 35 years as many as 371 people. Pregnant women with age <20 years old who haveplacenta previa as many as five people (14.7%) and age> 35 years old who have placentaprevia as many as 25 people (73.5%) more than the age of 20-35 years as many as 4 people(11.8%). There is a relationship between age and pregnant women with placenta previa. There is a relationship between age and pregnant women with placenta previa inBanyumas General Hospital in 2010 with a low relationship strength so that it can beconcluded that the incidence of placenta previa is not only caused by maternal age alone butalso due to other factors.Keywords: Age of Pregnancy, Placenta Previa.